The implications of population ageing on economic growth: Evidence of nonlinearity - Lobo, Charmaine Savia Siqueira; Falleiro, Savio da Piedade (Asian Economic and Financial Review, 2024)
The purpose of this study is to investigate the influence of population ageing on economic growth, a topic that has received inconclusive results. The Fixed Effects Model is used to analyze 5-year non-overlapping growth regressions on a panel of 72 nations spanning three decades. Data is extracted from the World Bank database and Penn World Tables. Findings indicate that in the short-run, population ageing positively impacts economic growth; nevertheless, a nonlinear relationship is observed in the long-run, highlighting the existence of a threshold. The findings remain robust upon proxying the old-age dependency ratio for the share of the elderly. The study identifies the threshold below (above) at which ageing populations impact economic growth positively (negatively). Marginal Effects support our findings, establishing that the detrimental effect on growth intensifies as ageing deepens. The research also identifies a notable nonlinear relationship between economic growth and population ageing in developed economies. Policy implications such as promoting healthy ageing, longer working years, encouraging savings, enhancing productivity via capital investments, and contributions of experienced older workers to the knowledge economy will facilitate reaping the silver demographic dividend and will help nations cope with and minimize the adverse impact of population ageing on economic growth.